Micromorphological evidence of warm-based glacier deposition from the Richer Hills Tillite (Victoria Land, Antarctica) - BARONI, CARLO; Fasano F. (Quaternary Science Reviews, 2006)
Thin sections of impregnated samples were used for micromorphological analysis of the ‘Ricker Hills Tillite’ in southern Victoria Land, Antarctica. The tillite is composed of massive matrix-supported diamicton with a porphyric coarse/fine related distribution, low sorting, low rounding and medium to high angularity. Glacial deposits are completely represented by lodgement till. Phyllosilicate reorientation patterns (plasmic fabrics) are visible in most samples, especially associated skelsepic and lattisepic patterns. Syndepositional pervasive till shearing (glacially induced) is evidenced by clast alignments, shear planes, rotational structures and pressure shadows. Boudinage, ductile shear zones, and rotational structures are also widespread in the deformed bedrock. Water-escape structures are clearly evident in the tillite and in the bedrock. Shear planes infilled by injection veins in lodgement till and at the till-bedrock interface testify to the presence of water during deposition. Secondary features like clay and silt coatings, sparite calcite, and oxidation products were found in all the examined outcrops. They formed under phreatic conditions due to saturated water circulation. A warm-based ice sheet was responsible for the deposition of the tillite. Past ice-flow directions were similar to present ones.